Carbon monoxide poisoning: easy to treat but difficult to recognise. - Balzan, M. V. (BMJ Group, 1996)
Carbon monoxide (CO) poisoning is a common medical emergency and a frequent cause of deliberate or accidental death. It can cause acute and chronic central nervous system damage which may be minimised by prompt treatment with 100% oxygen or hyperbaric oxygen therapy. However, recognition of this intoxication can be difficult. Failure to diagnose it may have disastrous effects on the patient, and other members of the household who could subsequently become intoxicated. Guidance on the correct diagnosis of this condition is provided in the light of a number of studies screening emergency room populations. Guidelines for treatment with hyperbaric oxygen therapy are also reviewed.